Job Displacement and Fertility over the Business Cycle - Arne Uhlendorff; Barbara Hofmann; Michaela Kreyenfeld (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We analyze the impact of job displacement on women s first birth rates and its variation over the business cycle. We exploit mass-layoffs to estimate the impact of involuntary unemployment on fertility in the short- and medium-run up to five years after displacement. The analysis is based on rich administrative data from Germany with an observation period spanning more than 20 years. We find evidence for adverse effects of job displacement on fertility. Our results suggest that the impact of a job loss is stronger in an economic downturn. Compared to job displacements in times of low unemployment rates, women loosing their job in times of high unemployment rates have a significant reduction in the probability of having a first child even five years after the displacement. These results do not seem to be driven by a changing composition of displaced women over the business cycle and they suggest that the opportunity costs of having a child are higher when the probability of finding a (good) job is lower.
Keywords: J13; J64; J65; 330